Validitas dan praktikalitas modul fisika mengintegrasikan literasi baru pada materi kalor dan teori kinetik gas untuk siswa kelas XI SMA - Naurah Nazifah; Asrizal Asrizal; Fatni Mutfit; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2020)
The industrial revolution 4.0 requires humans to possess 21st century skills. The 21st century education requires skills to develop superior knowledge, skills, attitude and values, which fully support it with literacy. Student literacy will be able to help the learning process, so students can apply learning material to the facts that are around it. One of literacy to answer the defiance of this era is the new literacy. New literacy consist data literacy, technology and human data. The reality at school was not as expected, the learning resources used by students weren’t entirely in accordance with the new literacy. Solution to solve problem was physics module integrated new literacy. The purpose of this reserch is to determine the validity and practicality use of physics modules. The type of research carried out includes the type of Research and Development (R&D). The object of this research was a physics module that integrates new literacy which is tried to be limited to one of the XI classes of SMA Pembangunan Lab UNP. The data analysis technique used was a descriptive analysis of the validity of the product and the practicality of the product. Based on data analysis from the research that has been done, it can be stated two results of this research, : First, validation of  a physics module can be classified in to very good categoy with a average value 86.2.  Second, practcality of the use physics module integrates new literacy by the teacher was  91.7 and practicality by student was 85.3 according to the category of practice very good.